Formal and Informal Assets in the Italian Labour Market - Francesca Borgonovi; Daniele Checchi; Valentina Gualtieri (Institute of Labor Economics (IZA), 2025)
This paper estimates labour-market returns to formal and informal human capital in Italy using data from the first cycle of PIAAC. We distinguish formal inputs (years of schooling) from directly assessed skills (literacy and numeracy) which we interpret as distinct forms of human capital that are shaped by school quality and by non-formal and informal learning. To address non-random employment and joint endogeneity of schooling and skills, we combine a Heckman selection model with instrumental variables. Schooling is instrumented using cohort exposure to the 1971 introduction of full-day primary schooling and the 1999–2001 Bologna '3+2' university reform; skills are instrumented using gender- and cohort-specific municipal illiteracy rates from population censuses, matched by birthplace. Results show that ignoring selection and endogeneity overstates the returns to schooling. After correction, numeracy yields the main wage premium, while formal credentials contribute little once skills are accounted for. The findings highlight the role of early cultural environments and skill accumulation for Italian wage inequality in Italy.
Keywords: J24; I26; 330; skill; schooling; credentials; Italy